PENGARUH JUMLAH DAUN DAN MACAM MEDIA TANAM PADA PERTUMBUHAN STEK JERUK NIPIS (Citrus aurantifolia Swingle) - Fitria Wulandari; Murti Astiningrum; Tujiyanta Tujiyanta (JURNAL VIGOR, 2017)
A research on the effect of the number of leaves on cuttings and kinds planting media on the growth of lime (Citrus aurantifolia Swingle), conducted in July to November 2014.The research location is at Kaliboto Village, District Bener, Purworejo. The altitude is150, the soil is regosol soil and soil pH is 6.0. The method used is a factorial experiment (3x4) arranged in complete randomized block design with 3 replications. The first factor is the number of leaf on cuttings 0, 2, 4 leaves. The second factor is planting media: soil; soil added cocopeat; soil added husk; soil added cow manure (1: 1). The analysis showedcuttingswithtwoleavesare able to providethe highest parameter son shoots length, number of leaves, root length, buds fresh weight, buds dry weight, root fresh weight and dry weight of root cuttings. Media of soil added husk isable to increase shoots length, number of leaves, buds fresh weight, bud dry weight, root fresh weight and dry weight of root cuttings. The different number of leaves on different kinds planting media indicate different growthon all parameters observed exceptroot length.